Widespread Biomass Burning Smoke Throughout the Remote Troposphere - Froyd, K D; Bian, H; Kupc, A; Williamson, C; Brock, C A; Ray, E; Hornbrook, R S; Hills, A J; Apel, E C; Chin, M; Colarco, P R; Murphy, D M (Nature geoscience, 2020)
Biomass burning emits ~34–41 Tg yr−1 of smoke aerosol to the atmosphere. Biomass burning aerosol directly influences the Earth’s climate by attenuation of solar and terrestrial radiation; however, its abundance and distribution on a global scale are poorly constrained, particularly after plumes dilute into the background remote troposphere and are subject to removal by clouds and precipitation. Here we report global-scale, airborne measurements of biomass burning aerosol in the remote tropo-sphere. Measurements were taken during four series of seasonal flights over the Pacific and Atlantic Ocean basins, each with near pole-to-pole latitude coverage. We find that biomass burning particles in the remote troposphere are dilute but ubiquitous, accounting for one-quarter of the accumulation-mode aerosol number and one-fifth of the aerosol mass. Comparing our obser-vations with a high-resolution global aerosol model, we find that the model overestimates biomass burning aerosol mass in the remote troposphere with a mean bias of >400%, largely due to insufficient wet removal by in-cloud precipitation. After updat-ing the model’s aerosol removal scheme we find that, on a global scale, dilute smoke contributes as much as denser plumes to biomass burning’s scattering and absorption effects on the Earth’s radiation field.